THE USE OF SOCIAL MEDIA: METAPHORICAL EUPHEMISM IN INDONESIAN PRESIDENT’S FACEBOOK COMMENTS - Haryanto, Sigit; Setiawaty, Rani; Rahmatika, Laily; Wahyudi, Agus Budi; Hoque, Mohammed Shamsul; Najikhah, Fatikhatun; Islam, M. Monjurul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
In this era of digitalization, national politicians are increasingly embracing social media as a means of effective communication with the people they govern. Social media platforms like Facebook have become customary for the ruling class to ensure efficient communication with the public. In their comments on social media, netizens frequently resort to metaphors to express their opinions on topics of general interest. This research examines the usage of metaphorical euphemisms in online comments on Joko Widodo's Facebook posts. This research aims to describe metaphorical euphemisms in President Joko Widodo's Facebook comments. A qualitative approach combined with content analysis has been used in this study. The results reveal that netizens' use of metaphorical euphemisms is influenced by their beliefs, experiences, and socio-cultural perceptions of politics. This study bridges a gap in the literature by investigating how national leaders, particularly in Indonesia, utilize rhetorical strategies on their social media accounts.